2019
DOI: 10.1021/acs.nanolett.9b01300
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of InP Twinning Superlattice Nanowires

Abstract: Taper-free InP twinning superlattice (TSL) nanowires with an average twin spacing of ~ 13 nm were grown along the zinc-blende close-packed [111] direction using metalorganic vapor phase epitaxy. The mechanical properties and fracture mechanisms of individual InP TSL nanowires in tension were ascertained by means of in situ uniaxial tensile tests in a transmission electron microscope. The elastic modulus, failure strain and tensile strength along the [111] direction were determined. No evidence of inelastic def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Chen et al reported that a high density of stacking faults in wurtzite GaAs nanowires resulted in an increased modulus, while Liu et al concluded that the opposite was true for WO 3 nanowires . In composition‐tunable alloy compounds, such as Si 1‐ x Ge x , the Young's modulus is presented as Y 110 = (169–31 x ) GPa along the [110] direction . The Young's modulus of Si 1‐ x Ge x [111] NWs was investigated through tensile stress measurements as a function of the Ge concentration with a mechanical testing system integrated on an SEM platform (Figure B) .…”
Section: Nanowire Mechanicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al reported that a high density of stacking faults in wurtzite GaAs nanowires resulted in an increased modulus, while Liu et al concluded that the opposite was true for WO 3 nanowires . In composition‐tunable alloy compounds, such as Si 1‐ x Ge x , the Young's modulus is presented as Y 110 = (169–31 x ) GPa along the [110] direction . The Young's modulus of Si 1‐ x Ge x [111] NWs was investigated through tensile stress measurements as a function of the Ge concentration with a mechanical testing system integrated on an SEM platform (Figure B) .…”
Section: Nanowire Mechanicsmentioning
confidence: 99%
“…131 In compositiontunable alloy compounds, such as Si 1-x Ge x , the Young's modulus is presented as Y 110 = (169-31x) GPa along the [110] direction. 20 The Young's modulus of Si 1-x Ge x [111] NWs was investigated through tensile stress measurements as a function of the Ge concentration with a mechanical testing system integrated on an SEM platform ( Figure 9B). 134 As shown in Figure 9C, left, the Young's modulus gradually decreases with increasing Ge content, which indicates an approximately linear relation with the relative compositions of Si and Ge.…”
Section: Young's Modulus and Fracture Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…To simplify the process, alternative fabrication routes were actively explored based on nanomaterials such as bottom-up nanowires (NWs) [4][5][6][7][8][9][10][11][12][13]. NWs not only have remarkable optoelectronic properties, but they can also withstand high deformations without plastic relaxation [14,15]. These properties motivated the intense research of NW flexible LEDs [4,[8][9][10][11][12][13]16].…”
Section: Introductionmentioning
confidence: 99%